A Psycholinguistic Study of Psychopathic Offenders’ Speech - Rasheed, Nareeman Jabbar (Journal of Educational and Psychological Sciences, 2020)
The present study aims at studying the psychopathic speech of offenders and analyzing their behavior by using psycholinguistics. The following study involved a psycholinguistic analysis of psychopathic offenders’ speech. The research design was chosen to be descriptive and involved an observation of three offenders based on interviews done with them on YouTube. The descriptive model to be followed in analyzing the psychopathic offenders personality features is that of Hare (2003), and Hare et al's (1988).The first finding was that psychopaths were more likely than their counterparts to use explanatory and causally framed language concerning their criminal actions, with a relatively high level of subordinating conjunctions, indicating more cause and effect statements. This pattern suggested that psychopaths were more likely to have viewed the crime as a logical outcome of a plan (something that ‘had’ to be done to achieve a goal), their violence is indeed more instrumental and goal driven than that of other offenders. Secondly, we found that psychopaths used approximately twice as many words related to basic physiological and self-preservation needs, including eating, drinking, and money when describing their violence. This pattern is consistent with conceptualizations of psychopaths as being focused on a lower level of necessities, hierarchy of needs or in an earlier stage of ego development. Psychopaths generally lack the capacity for bonds and, presumably, the capacity for religious experience or spiritual enlightenment. As such, they continue to describe the crime in a cool, detached manner and in terms of the basic physiological needs they met at the time.
Keywords: psycholinguistic analysis; offenders' speech; psychopaths